2021
DOI: 10.3390/ijerph18052630
|View full text |Cite
|
Sign up to set email alerts
|

Sounds That People with Visual Impairment Want to Experience

Abstract: This article presents the expectations of visually impaired people with regard to the content of a set of sound exercises planned for implementation, which will mainly enable these people to become familiar with the sounds associated with specific life situations. Consultations were carried out with 20 people with visual impairment, which allowed for the recognition of the needs of these people regarding the sounds with which they wish to become acquainted. The 35 initially proposed sounds were assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…For persons with disabilities (visual disability), embarking on any journey starts with information as they need to be certain that the entire journey is accessible before they set out on a trip, this is important since they cannot adapt easily to the barriers they may encounter (Park & Chowdhury, 2018). It is known that the reception of auditory stimuli plays a very important role in the functioning of people with visual impairment (Mlynski et al, 2021), therefore, making all information that aids public transport auditory would be beneficial as suggested by some studies in this current review (Fürst, 2010;Golledge et al, 1997;Hersh, 2016;Park et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For persons with disabilities (visual disability), embarking on any journey starts with information as they need to be certain that the entire journey is accessible before they set out on a trip, this is important since they cannot adapt easily to the barriers they may encounter (Park & Chowdhury, 2018). It is known that the reception of auditory stimuli plays a very important role in the functioning of people with visual impairment (Mlynski et al, 2021), therefore, making all information that aids public transport auditory would be beneficial as suggested by some studies in this current review (Fürst, 2010;Golledge et al, 1997;Hersh, 2016;Park et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…ze środowiskiem pracy. Zawartość zbioru dźwięków była przedmiotem konsultacji, które odbyto z udziałem 20 osób z niepełnosprawnością narządu wzroku [11]. Sugestie przekazane w trakcie tych konsultacji wykorzystano podczas ustalania zawartości zbioru materiału dźwiękowego.…”
Section: Zbiór Dźwiękówunclassified
“…Various studies have shown that people who are visually impaired show higher levels of auditory ability due to their frequent use in this population. These abilities are pertinent to auditory skills such as echo processing, voice localizing, and distance estimation [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%